Implementing non-invasive prenatal testing into publicly funded antenatal screening services for Down syndrome and other conditions in Aotearoa New Zealand - Sara Filoche; Fiona Cram; Bev Lawton; Angela Beard; Peter Stone (BMC, 2017)
Abstract Background Non-invasive prenatal testing (NIPT) is a relatively new screen for congenital conditions - specifically, common fetal aneuploidies including Down Syndrome. The test is based on isolating freely circulating fragments of fetal-placental DNA that is present in the mother's blood. NIPT has a superior clinical performance compared to current screening, and has been available privately in Aotearoa New Zealand for the last 4 years. Main issue The proposed implementation of NIPT as a publicly funded service may widen the inequity in access to optional antenatal screening that already exists in this country. Conclusion This paper discusses precautions that can be taken at the health system, organisation, and personnel levels to ensure that access to NIPT is equitable, that services are culturally responsive, and women's informed choice is promoted and protected. The adoption of NIPT into publicly funded services is an example of how genetic screening is becoming mainstreamed into health services; as such our approach may also have relevance around the introduction of other genetic and genomic screening initiatives.